Implementasi Metode Nidzomi Karya Kang Syuhada: Analisis Proses Pembelajaran Nahwu Shorof di Pesantren Nurul Huda Bendagede Kawunganten Cilacap - Khoirurotun; Fathurohim (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2026)
This study analyzes the implementation of the Nidzomi Method developed by Kang Syuhada in teaching Arabic grammar (Nahwu Shorof) at Pondok Pesantren Nurul Huda. The complexity of Arabic grammatical rules often becomes a major obstacle for students in understanding classical Islamic texts (Kitab Kuning), thus requiring a more effective and easily internalized learning approach. The Nidzomi Method emerges as a didactic innovation by transforming Nahwu Shorof rules into rhythmic poetic verses (nadzom) that function as mnemonic learning tools. This study employed a qualitative approach using a Critical Case Study design. Data were collected through interviews, participant observation, and document analysis. The findings reveal that the implementation of the method is conducted systematically through three learning phases: Pre-Nadzom (concept introduction), Core Nadzom (internalization of rhythm and text), and Post-Nadzom (application and contextualization of grammatical rules). The instructional strategy is supported by visual mapping and nadzom-centered correction techniques, which significantly improve students’ memorization, learning motivation, and practical application of Nahwu Shorof rules. The main contribution of this study lies in the development of a structured and contextual nadzom-based instructional model for teaching Nahwu Shorof, while also enriching Islamic boarding school pedagogy through the integration of mnemonic methods, musicality, and grammatical application in the teaching of Kitab Kuning. This study concludes that the Nidzomi Method is an effective and feasible alternative for revitalizing Arabic grammar instruction in Islamic boarding schools.